The Impact of Cardiac Rehabilitation on Activities of Daily Life in Elderly Patients With Heart Failure - Paneroni, Mara; Scalvini, Simonetta; Corrà, Ugo; Lovagnini, Marta; Maestri, Roberto; Mazza, Antonio; Raimondo, Rosa; Agostoni, Piergiuseppe; La Rovere, Maria Teresa (Frontiers in Physiology, 2022)
Background. In elderly chronic heart failure (HF) patients, activities of daily living (ADLs) require the use of a high proportion of patients’ peak aerobic capacity, heart rate and ventilation. Objectives. To assess the effects of short-term comprehensive cardiac rehabilitation (CR) on the metabolic requirement of ADLs in elderly patients with chronic HF. Methods. The study population comprised 99 elderly chronic HF patients (mean age 72±5 years, 80% male, 61% ejection fraction <40%, mean NT-proBNP 2559±4511 pg/mL) participating in a short-term (mean days 19±7) residential CR program. Before and after CR, participants while wearing a portable ergo spirometer, performed a standardized ADL battery: ADL1 (getting dressed), ADL2 (folding 8 towels), ADL3 (putting away 6 bottles), ADL4 (making a bed), ADL5 (sweeping the floor for 4 minutes), ADL6 (climbing 1 flight of stairs carrying a 1.5 Kg load), ADL 7 (a standard 6-minute walking test). Results. After CR, task-related oxygen uptake did not change in any of the domestic ADLs. Notably, there was a significant decrease in the cumulative time required to perform ADLs (ADL 1-4 and ADL6) (from 412±147 to 388±141 seconds, p=0.001) and a reduction in maximal heart rate in ADL1 and 3 (p=0.005 and p=0.027, respectively). Changes occurred in the 6MWT with an increase in oxygen uptake (p=0.005) and distance covered (p<0.001) and a significant decrease in the Borg scale of dyspnea (p=0.004). Conclusions. Elderly patients with chronic heart failure who are engaged in a short-term residential CR program improve the performance of routine activities of daily living.